To the question of determining glycemic index by glucose - I. S. Vitol; E. P. Meleshkina; G. N. Dubtsova (Пищевые системы, 2021)
The analysis of methods for determining the glycemic index (GI) of food products in vivo and in vitro. The authors note that the difference in the methodological approach to the determination of GI in vitro leads to obtaining results that are difficult to compare. A modified method for determining the GI for glucose is proposed, which is based on the method for determining the glycemic index for glucose, which makes it possible to assess the digestibility of various ingredients in products in terms of sugar load, and to calculate the glycemic index for glucose formed in the process of "digestion” of the test product in vitro. The modified technique provides for the use of digestive enzyme preparations: Acedin-pepsin and Panzinorm to provide a deeper "digestion” in vitro, providing a deep degree of hydrolysis of the main macronutrients in in vitro model experiments. The conditions for carrying out enzymatic hydrolysis reactions (temperature, pH, reaction duration) were selected experimentally. The studies carried out to determine the GI in vitro, according to the proposed method, showed comparable values, which indicates the possibility of using this method for the determination of GI in vitro. The results obtained should be considered as indicative, since the authors adhere to the position that the true value of the GI index can only be determined by blood analysis. But in this case, the value of GI is influenced by many factors, including the individual characteristics of the human organism.